METHODOLOGICAL RECOMMENDATIONS for independent and practical work on the subject «METAL STRUCTURES DESIGN» (special course) (for all educational forms Bachelor’s Degree students on specialty 192 – Building Industry and Civil Engineering, of educational program “Civil and Industrial Engineering”) - О. Lugchenko; P. Firsov; О. Kulakov; О. Kalmykov (O. M. Beketov NUUE, 2023)
The purpose of independent work of applicants is to study the theoretical part of the course in depth, to acquire the skills of calculation and construction of elements and joints of steel structures in accordance with current design standards, as well as the skills of using normative and reference literature.
Keywords: design of metal structures; MS elements